Atrial fibrillation for internists: current practice (Swiss Medical Weekly, 2020)
Atrial fibrillation (AF) has become a global epidemic and puts affected patients at high risk of adverse events. In this review we summarise the current evidence on risk factors and complications of AF, describe current treatment strategies, and outline new fields of research. Current evidence shows that hypertension and obesity are the two most important modifiable risk factors for the development of AF. Patients with AF face an increased stroke risk. Oral anticoagulation reduces this risk substantially. Mainly for reasons of safety and ease of use, non-vitamin K antagonist oral anticoagulants are preferred for stroke prevention. Rate and rhythm control interventions remain important and are mainly used for symptom control in AF patients. Rate control is recommended as an initial treatment and in patients with a low or absent symptom burden. Following the advent of AF ablation 20 years ago, the chances of successful sustained rhythm control have increased. Nevertheless, the procedural risks, although low, must be discussed with the patient in the context of the potential benefits. Heart failure and AF often coexist, which creates a further challenge for optimal AF management. Recent studies have shown that AF patients have a high burden of silent brain lesions, and that these lesions are associated with cognitive dysfunction. A better understanding of these interrelationships may eventually help the development of new prevention and treatment strategies to decrease the burden and complications associated with AF.